Crystallographic analysis of Eisenia hydrolysis‐enhancing protein using a long wavelength for native‐SAD phasing. Issue 1 (13th January 2020) - Sun, Xiaomei; Ye, Yuxin; Sakurai, Naofumi; Kato, Koji; Yuasa, Keizo; Tsuji, Akihiko; Yao, Min
Abstract : Eisenia hydrolysis‐enhancing protein from Aplysia kurodai, which is of interest as an indispensable protein for aiding the production of glucose from brown algae, has been purified and crystallized. Native and native‐SAD X‐ray diffraction data were collected at resolutions of 1.20 and 2.48 Å using wavelengths of 1.0 and 2.1 Å, respectively. Abstract : Eisenia hydrolysis‐enhancing protein (EHEP), which is a novel protein that has been identified in Aplysia kurodai, protects β‐glucosidases from phlorotannin inhibition to facilitate the production of glucose from the laminarin abundant in brown algae. Hence, EHEP has attracted attention for its potential applications in producing biofuel from brown algae. In this study, EHEP was purified from the natural digestive fluid of A. kurodai and was crystallized using the sitting‐drop vapor‐diffusion method. Native and SAD (single‐wavelength anomalous diffraction) data sets were successfully collected at resolutions of 1.20 and 2.48 Å using wavelengths of 1.0 and 2.1 Å, respectively, from crystals obtained in initial screening. The crystals belonged to space group P 21 21 21 and contained one EHEP molecule in the asymmetric unit. All 20 S‐atom sites in EHEP were located and the phases were determined by the SAD method using the S atoms in the natural protein as anomalous scatterers (native‐SAD). After phase improvement, interpretable electron densities were obtained and 58% of the model was automatically built.